2022
DOI: 10.3390/plants11233280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Germplasm of Cultivated Oat Species from the VIR Collection under the Russian Northwest Conditions

Abstract: Oat is one of the most widespread and important cereal crops in the global agricultural production. Searching for new high-yielding and nutritious forms continues to be relevant, especially under the global trend of climate change, when most local oat cultivars may become economically inefficient. Spring oat accessions from VIR collection served as the material for this study; their origin is diverse, as they came from 11 countries. The basic nutritional value (the content of protein, oil, starch, and β-glucan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…A significantly lower variability in β-D-glucan contents was confirmed among four oat species A. sativa (3.60%), A. byzantina (3.40%), A. abyssinica (2.46%), and A. strigosa (2.97%) by the recent study of VIR oat collection by Popov et al [ 52 ]. These results indicated that the hexaploid cultivated oat species A. sativa and A. byzantina showed a generally higher content of β-D-glucans than tetraploid and diploid wild accessions.…”
Section: Content Of β-D-glucans In Grains Of Poalesmentioning
confidence: 85%
“…A significantly lower variability in β-D-glucan contents was confirmed among four oat species A. sativa (3.60%), A. byzantina (3.40%), A. abyssinica (2.46%), and A. strigosa (2.97%) by the recent study of VIR oat collection by Popov et al [ 52 ]. These results indicated that the hexaploid cultivated oat species A. sativa and A. byzantina showed a generally higher content of β-D-glucans than tetraploid and diploid wild accessions.…”
Section: Content Of β-D-glucans In Grains Of Poalesmentioning
confidence: 85%
“…Приводим некоторые статьи за период с 2016 по 2022 г. (Grigorev et al, 2022;Loskutov et al, 2022;Popov et al, 2022;Porokhovinova et al, 2022;Shelenga et al, 2021;Shvachko et al, 2021;Solovyeva et al, 2021;Bityutskii et al, 2020;Gavrilova et al, 2020;Loskutov et al, 2020;Shelenga et al, 2020;Sidorova et al, 2020;Konarev et al, 2019;Loskutov et al, 2019;Sidorova et al, 2018;Loskutov et al, 2017;Perchuk et al, 2016). А. В. Конарев -участник многих оте чественных и международных конгрессов, симпозиумов и совещаний.…”
unclassified
“…Popov et al evaluated the nutritional and agronomic value of 49 accessions of cultivated oat species maintained in the VIR genebank [ 13 ]. Sources of useful agronomic traits were identified, which can be used to develop new high-yielding and highly nutritious oat cultivars adapted to local cultivation conditions.…”
mentioning
confidence: 99%